2013
DOI: 10.1186/1471-2229-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell-based system to monitor carrier driven cellular auxin homeostasis

Abstract: BackgroundAbundance and distribution of the plant hormone auxin play important roles in plant development. Besides other metabolic processes, various auxin carriers control the cellular level of active auxin and, hence, are major regulators of cellular auxin homeostasis. Despite the developmental importance of auxin transporters, a simple medium-to-high throughput approach to assess carrier activities is still missing. Here we show that carrier driven depletion of cellular auxin correlates with reduced nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Studies done with ectopically expressed PIN5 have shown that PIN5 localizes predominantly in the ER and is involved in intracellular auxin homeostasis by possibly transporting cytosolic auxin to the ER lumen (Mravec et al, 2009;Ganguly et al, 2010;Barbez et al, 2013). In this study, we observed that PIN5 can also localize to the PM and undergoes endocytosis in certain cell types, including its own expression domain.…”
Section: Pin5 May Act As a Dual Regulator For Intracellular And Intersupporting
confidence: 54%
“…Studies done with ectopically expressed PIN5 have shown that PIN5 localizes predominantly in the ER and is involved in intracellular auxin homeostasis by possibly transporting cytosolic auxin to the ER lumen (Mravec et al, 2009;Ganguly et al, 2010;Barbez et al, 2013). In this study, we observed that PIN5 can also localize to the PM and undergoes endocytosis in certain cell types, including its own expression domain.…”
Section: Pin5 May Act As a Dual Regulator For Intracellular And Intersupporting
confidence: 54%
“…S15), suggesting that the localization of NBDauxins was not due to the nonspecific binding of the NBD fluorophores to organelles or membranes. Several auxin transporters, such as PIN5, PIN8, and PILS, are subcellularly localized to the endoplasmic reticulum (ER) (34)(35)(36). NBD-auxin signals showed a similar localization pattern to the signals of PIN5-GFP and PIN8-GFP observed in BY-2 cells (Fig.…”
Section: Fluorescent Auxin Distribution Mimics Native Auxin Accumulatmentioning
confidence: 57%
“…These results imply that NBD-auxins might aggregate locally at application sites; therefore, NBD-auxins are not versatile for the visualization of auxin transport streams in the shoot. Several ER-localized auxin transporters, such as PIN5, PIN8, and PILS, play a role in subcellular auxin homeostasis (34)(35)(36). Because of the general nature of small-molecule compounds, a small fraction of NBDauxins might be passively diffused and nonspecifically bound to organelle membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agravitropic pin2 phenotype along with the polarized localization of PIN2 in the root identified PIN2 as the PAT component of root gravitropic response. The auxin efflux capacity of PIN proteins has since been shown in a number of transport assays in different systems (Petrásek et al, 2006;Yang and Murphy, 2009;Barbez et al, 2013;Zourelidou et al, 2014). An important question concerned the relation between PIN polarity and directionality of auxin transport.…”
Section: Discovery Of Pins: the Polarized Auxin Efflux Components Prementioning
confidence: 99%